GENDER-BIAS DALAM INTERAKSI PEMBELAJARAN: ANALISIS PENYEBAB RENDAHNYA PARTISIPASI BELAJAR MURID LAKI-LAKI DI KELAS DI SMA NEGERI 1 PANYABUNGAN - Kartika, Syahra; Adji Putrah; Muhammad Razali; Isla Khairani; Khafifah Nur Rangkuti; Alia Arfina; Rinawanti Tan; Ramandha Putri Daulay; Putri Wahyuni Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze gender bias in classroom interaction and the factors contributing to the low participation of male students in classroom learning at SMA Negeri 1 Panyabungan. This research employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that teachers tend to be more responsive to female students in classroom discussions, academic appreciation, and verbal interaction. Furthermore, gender stereotypes, teacher communication patterns, and classroom learning culture influence the low participation of male students. The study concludes that gender bias in classroom interaction contributes to unequal learning participation and highlights the need for more inclusive and gender-responsive teaching strategies.